Correction: Autophagy buffers Ras-induced genotoxic stress enabling malignant transformation in keratinocytes primed by human papillomavirus - Cararo-Lopes, Eduardo; Dias, Matheus H.; da Silva, Marcelo S.; Zeidler, Julianna D.; Vessoni, Alexandre T.; Reis, Marcelo S.; Boccardo, Enrique; Armelin, Hugo A. (Springer Nature, 2021)
The original version of this article unfortunately contained an error in the affiliations. The affiliations were not correctly assigned to the authors. The original article has been corrected.
Correction: Autophagy buffers Ras-induced genotoxic stress enabling malignant transformation in keratinocytes primed by human papillomavirus (Cell Death & Disease, (2021), 12, 2, (194), 10.1038/s41419-021-03476-3)